ANALISIS AZAS MANFAAT DAN AKAD PINJAMAN ONLINE DALAM PERSPEKTIF EKONOMI SYARIAH: STUDI LITERATUR - Beatrixs Sugi Santoso Putri (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
Technological sophistication is overgrowing to make it easier for humans in all their activities. One sector that takes advantage of technological sophistication is financial services. P2P lending refers to the provision of financial services that bring together lenders and loan receivers in the context of engaging into loa and borrowing agreements cia an electronic system that uses the internet network. The ease of the P2P Lending service offered by this online loan is very tempting for users. However, many Muslim people are still unwilling to do so. This study purposes to establish the principle of benefits and online loan agreements from an Islamic economic perspective. This research type is descriptive qualitative research using a systematic literature review. The research data is from 6 journals related to online lending from the perspective of Islamic economics published in 2020-2022. The study results show that online lending, or P2P lending, is a form of financial service utilizing technological sophistication. Online loans are permissible according to Sharia, but with various conditions that do not violate Sharia rules by MUI Fatwa No.117/DSN-MUI/II/2018. The principle of the benefits of giving loans in Islam is permissible to people who need debt to fulfill their needs based on mutual help in good matters. According to the Islamic economy, online loan transactions are classified as accounts payable (Qarḍh). In Islam, qardh is valid if the parties fulfill the conditions and pillars. If one of the conditions and pillars is not fulfilled, the qardh contract becomes invalid. Thus, the debts are considered to have occurred if the pillars and conditions of the debts themselves have been fulfilled.